Impacts of dredging on biomarkers responses of caged bivalves in a semi-arid region (Ceará State, NE Brazil) - Moreira, Lucas B. [UNESP]; Sasaki, Silvio T.; Taniguchi, Satie; Bícego, Márcia C.; Costa-Lotufo, Leticia V.; Abessa, Denis M.S. [UNESP] (Elsevier, 2019)
In this study, the performance of two native bivalves in responding to sediment resuspension was investigated during dredging operations of a semi-arid bay (Mucuripe, NE Brazil). The clam Anomalocardia flexuosa and the oyster Crassostrea rhizophorae were selected and caged in two sites influenced by the dredging plume. We assessed the bioaccumulation of metals and hydrocarbons in both species as biomarkers of exposure and then, biomarkers’ responses were assessed in gills and digestive glands over a 28 days period, at 7 days intervals: the activities of phase I and II, and antioxidant enzymes, levels of lipid peroxidation and DNA strand breaks. Both transplanted bivalves accumulated Cu, polycyclic aromatic hydrocarbons (PAHs), and linear alkylbenzenes (LABs) in their whole-body tissues, whereas Ni, Pb and Zn accumulation was species-dependent. The exposure time set at day 28 was considered appropriate. Biomarkers exhibited time-related responses in both species, but gills exhibited a more sensitive response, indicating a function of barrier against the uptake of chemicals and also a relevant tissue to be targeted. In clams, Phase I and II enzymes (ethoxyresorufin O-deethylase and glutathione S-transferase) were induced during the period of intense dredging, while in oysters they were activated at the end of operations. Induction of antioxidant enzymes (glutathione peroxidase and glutathione reductase) and elevated levels DNA damage were observed in both exposure surveys. Clams and oysters were sensitive and responded to the exposure of resuspended sediments and the biomarkers of effects were associated with bioaccumulation of contaminants in the integrated analysis. These results indicate that The clam A. flexuosa and the oyster C. rhizophorae are suitable models to be used in monitoring programs or field exposure experiments in tropical regions.
Keywords: Environmental management; Environmental monitoring; Marine pollution; Sediment; Tropical environments; Tropical species